Metabolic Responses, Uptake, and Export of Copper in Cyanobacteria - Jean Coutinho Oder; Thamires Emidio Sateles; Laila Barros de Souza; Adriano Nunes-Nesi; Wagner L. Araújo; Luna Alvarenga-Lucius (Biology, 2025)
Copper (Cu) is an essential micronutrient for cyanobacteria, where it functions as a cofactor in key proteins involved in photosynthesis and antioxidant defense. However, at elevated concentrations, Cu becomes toxic, exhibiting algicidal effects by disrupting metal homeostasis and competing for metal-binding sites on critical cellular proteins. Due to the considerable morphological and physiological diversity within the phylum Cyanobacteria, the thresholds for Cu deficiency or toxicity vary considerably among strains. Maintaining Cu homeostasis in cyanobacterial cells is a complex process involving multiple layers of regulation. It begins at the extracellular polysaccharide layer, involves specialized membrane-bound proteins (in the outer, plasma, and thylakoid membranes), and results in transcriptional regulation in response to intracellular Cu status. This review summarizes the current understanding of Cu uptake and efflux pathways in cyanobacteria and explores how these mechanisms contribute to maintaining cellular Cu balance. The knowledge gained may contribute to the application of cyanobacteria in bioremediation strategies and/or the targeted use of Cu in the control of harmful cyanobacterial blooms.